Abrasion resistance and thermal conductivity of ZrO2-containing bauxite refractories in the transition zone of a cement kiln. Issue 15 (15th October 2018) - Ren, Bo; Li, Yawei; Nath, Mithun; Yan, Shu; Wang, Qinghu
Abstract: To substitute bauxite-SiC refractories which are currently used in transition zone of cement kilns, this paper aims to fabricate novel working lining with lower thermal conductivity and outstanding abrasion resistance. For this purpose, a composite refractory material, based on the incorporation of zircon and fused zirconia-mullite (FZM) into bauxite-based refractories is fabricated. The addition of both zircon and FZM led to superior thermal insulation performance despite their different abrasion behaviours. In particular, specimen containing zircon possesses lower cold crushing strength and accordingly inferior abrasion resistance, as compared to bauxite-SiC refractories. By comparison, incorporation of FZM powder resulted in the best abrasion resistance, as it is related to the improved fracture toughness which retard the propagation of crack, thereby preventing the material form spallation. ZrO2 -containing bauxite refractories can be promising materials to satisfy the new request of cement rotary kilns.